2012
DOI: 10.1177/0739456x11435511
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Planning for Change and Continuity in Botswana

Abstract: This paper examines how culture might be integrated in planning by critically rethinking the role of planners and knowledge in the planning systems of postcolonial contexts. The empirical study of cultural conception and utilization in Botswana suggests a shift from planning for culture to cultural institutionalization, where culture, rather than as an object, becomes integral to development planning decisions. The traditional division between bottom-up and top-down approaches is challenged, so as to allow a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Halvorson and Hamilton (2010) also confirmed that most houses that were affected by the earthquake in 2005 Kashmir, Pakistan, were due to poorly constructed structures situated in disaster-prone areas. Worst still, building codes are not enforced in most rural areas in Botswana especially small villages, and this compounds the problem (Hammami, 2012). The major weakness of this traditional structure, however, is that at times it is not built properly; there is no prescribed standard, and it differs from district to district This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…Halvorson and Hamilton (2010) also confirmed that most houses that were affected by the earthquake in 2005 Kashmir, Pakistan, were due to poorly constructed structures situated in disaster-prone areas. Worst still, building codes are not enforced in most rural areas in Botswana especially small villages, and this compounds the problem (Hammami, 2012). The major weakness of this traditional structure, however, is that at times it is not built properly; there is no prescribed standard, and it differs from district to district This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…It is outside our scope here to explore these global initiatives other than to note their relevance to the Maun context and the reality that poor public consultation and poor public understanding about land development is a common challenge to cultural sustainability worldwide (see Marcucci 2000 andHammami 2012 for two widely disparate examples) where more often than not officially planned developments override cultural spaces and features in a rural village like Maun. Cultural features that we identified during our research that do not appear in official planning maps are discussed in sections below.…”
Section: Modern Land-use Planning and Erasure Of Local Cultural Valuementioning
confidence: 98%
“…Spokespersons for cultural planning have claimed that culture and cultural planning should be given greater attention in development processes, during which we should be more aware of 'how culture might be integrated in planning by critically rethinking the role of planners and knowledge' (Hammami 2012a). The potential inherent in considering culture and cultural diversity in planning processes is undisputable and has been addressed in numerous studies, and methods for practising cultural planning abound in the form of handbooks and toolkits (Young and Stevenson 2013).…”
Section: Why Cultural Planning?mentioning
confidence: 99%